Views from the shore: An analysis of public comments on an offshore wind energy future in Nova Scotia, Canada - Ahern, Isabella; Walker, Chad; Roux, Jean-Pierre; Chateau, Zoé (Canadian Planning and Policy / Aménagement et politique au Canada, 2025)
Centered around concerns of climate change, energy security, and the need for low-cost clean electricity, many jurisdictions that have access to maritime areas are developing offshore wind energy. The province of Nova Scotia, Canada – home to some of the strongest offshore wind resources in the world – is one such place. Yet before development, governments need to listen, understand, and respond to the views of a diverse set of stakeholders, and affected publics. Using online and in-person open house comments, this exploratory study was conducted to determine the level and type of socio-political acceptance during the initial planning stages of offshore wind energy in Nova Scotia. Content analysis revealed that many people who participated in these consultations were initially ambivalent/unclear (with more opposed than supportive) – with regard to offshore wind energy. Consultees most opposed were Indigenous peoples/representatives, members of the general public, and Non-Government Organizations (NGOs). Thematic analysis identified six main themes, with the most referenced being concerns around biodiversity impacts and general environmental concerns. We close the paper with a discussion of the broader implications of our work, including relevance to future research, planning, and policy.